β-Tricalcium Phosphate Interferes with the Assessment of Crystallinity in Burned Skeletal Remains - Piga, Giampaolo (2018)
The analysis of burned remains is a highly complex process, and a better insight can be gained with advanced technologies. The main goal of this paper is to apply X-ray diffraction, partially supported by infrared attenuated total reflectance spectroscopy to determine changes in burned human bones and teeth in terms of mineral phase transformations. Samples of 36 bones and 12 teeth were heated at 1050°C and afterwards subjected to XRD and ATR-IR. The crystallinity index was calculated for every sample. A quantitative evaluation of phases was documented by using the Rietveld approach. In addition to bioapatite, the following mineralogical phases were found in the bone: β-tricalcium phosphate (β-TCP) (Ca3(PO4)2), lime (CaO), portlandite (Ca(OH)2), calcite (CaCO3), and buchwaldite (NaCaPO4). In the case of bone, besides bioapatite, only the first two mineralogical phases and magnesium oxide were present. We also observed that the formation of β-TCP affects the phosphate peaks used for CI calculation. Therefore, caution is needed when its occurrence and evaluation are carried out. This is an important warning for tracking heat-induced changes in human bone, in terms of physicochemical properties related to structure, which is expected to impact in forensic, bioanthropological, and archaeological contexts.